Evaluating Financial Performance in Times of Crisis: A Case Study of a Full-Service Hotel - Mei Lin Charisty Chang; Andre Hernowo; Pudin Saepudin (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2024)
Purpose of the study: This study aims to assess the financial performance of full-services hotel during the COVID-19 pandemic over the period 2019–2021. It examines the effects of the pandemic on the hotel’s profitability and identifies suitable strategies for financial recovery and sustainable operations in the post-pandemic context. Design/methodology: The research adopts a descriptive quantitative approach focusing on one of full-services hotel in city of Bandung, Indonesia. The main analytical tools are financial statements, particularly income statements, which are examined using horizontal, vertical, and trend analyses supported by Microsoft Excel. To enrich the analysis, interviews with hotel management and a review of relevant literature were conducted. Findings: The results show a marked decline in revenue and profitability during 2019–2021, the core pandemic years. The analysis also reveals rising operational costs and a generally weak financial position, underscoring the need for stronger cost-control measures and revenue-optimization strategies to improve financial performance in the post-pandemic period. Research limitations/implications: This study is relevant to hospitality management, financial analysis, and strategic planning, offering practical insights for hotel managers, financial analysts, and policymakers on evaluating financial performance in times of crisis. It also provides a reference point for future research on hotel management and recovery strategies in the tourism and hospitality industries. Novelty/originality of the study: This research presents a focused analysis of the financial performance of one full-services hotel in city of Bandung, Indonesia during the COVID-19 crisis, a period of extraordinary disruption for the hospitality sector. By applying a comprehensive quantitative framework and emphasizing financial recovery strategies, the study advances knowledge on crisis management and financial resilience and delivers actionable insights for industry stakeholders.